Estudo clínico, histológico e parasitológico do trato gastrintestinal de cães infectados com Leishmania (Leishmania) infantum - Aldair Junio Woyames Pinto (2014)
There are few descriptions of pathological and parasitological changes related to the involvement of the gastrointestinal (GIT) tract in canine visceral leishmaniasis especially systematically studies. Thus, this work aimed to a systematic study, pathological and parasitological GIT of dogs naturally infected with Leishmania (Leishmania) infantum. After serological confirmation (IFAT and ELISA) and parasitological (bone marrow smear), the dogs were divided clinically into three groups : symptomatic (n = 6) when the expression of at least one clinical sign suggestive of visceral leishmaniasis; asymptomatic (n = 6) when the absence of clinical signs and the uninfected control group (n = 3). The animals were provided by zoonoses center of Ribeirão das Neves andCarandaí, MG, Belo Horizonte metropolitan and non-endemic area of the disease, consecutively . The animals were euthanized and necropsied to collect the following segments of the GIT: esophagus, stomach , duodenum , jejunum , ileum , cecum , colon and rectum. Fragments of all segments cited were collected in triplicate and determined: (1) 10 % buffered formalin, (2)Carnoy 's solution and (3) absolute acetone . After fixation tissues were embedded in glycol methacrylate resin (GMA) andparaffin for routine histology staining and immunohistochemical reactions. GIT samples were used for staining (H & E) and special staining (toluidine blue ,Dominici and PAS). After standardization ofinclusion in GMA resin qualitative and quantitative (morphometric) using optical microscopy studies were performed. The main clinical signs of disease were exfoliative dermatitis and onychogryphosis . On microscopic examination, in all infected dogs, there was a remarkable increase in cellularity of the lamina propria and submucosa in all segments of the GIT compared with control dogs. Blades made oftissues embedding in GMA provided a morphological analysis with superior quality when compared to paraffin-embedded tissues, due to the higher cellular detail confirming the predominance of mononuclear cells diffusely located in the lamina propria (mucosa) and submucosa , represented by plasma cells , lymphocytes and macrophages. Polymorphonuclear cells such as neutrophils and eosinophils were rarely observed in all cases studied. Macrophages with peculiar morphology, large core (relative to other cells) with loose chromatin and large cytoplasm were visualized, sometimes vacuolated with large number of Leishmania amastigotes. Immunohistochemistry on tissue GMA was not satisfactory as compared to paraffin embedded tissues. Amastigotes were found in greater proportion in the large intestine (caecum, colon and rectum) and small intestine (stomach, duodenum,and ileum) . No markings of amastigotes in the esophagus and jejunum of infected dogs were found. The technique of embedding in GMA in canine tissue proved to be of great importance for the histological evaluations of samples of canine GIT, with a better result , especially as regards the special staining , especially when evaluated mast cells with toluidine blue. There was a reduction in these cells in every segment of infected dogs . Proved the epithelial atrophy in some segments ofinfected dogs when compared to controls . Thus, we conclude that the GMA histological technique is an excellent tool for morphological studies Histological samples of canine GITconfirm the presence of a diffuse chronic inflation throughout the GIT tract without formation of granulomas , which reduces the number of mast cells and epithelial atrophy in both asymptomatic and symptomatic dogs